Assessing the Reliability of D-Dimer Measurement in EDTA Plasma: A Comparison to the Established Citrate Method - Daniel Pfingst; Adriana Méndez; Peter Neyer; Henning Nilius; Nicole Schaub; Patricia Keusch; Michael Nagler; Angelika Hammerer-Lercher (Diagnostics)
Background: D-dimer determined in citrated plasma is a well-established and efficient biomarker, particularly for ruling out venous thromboembolism. In certain clinical settings, the availability of citrated plasma may pose challenges when not readily available. To address this issue, we investigated the feasibility of using ethylenediaminetetraacetic acid (EDTA) plasma as an alternative specimen for D-dimer measurement. Methods: Our study evaluated anonymized plasma samples (n = 99, for both citrate and EDTA) using the INNOVANCE® D-dimer assay, an automated particle-enhanced immunoassay, and the INNOVANCE® LOCI hs D-dimer assay, leveraging the luminescent oxygen channeling assay (LOCI) method. Results: The assays demonstrated a correlation of r ≥ 0.97 (95% CI 0.96 to 0.98) within citrated plasma and maintained a similar correlation r ≥ 0.96 (95% CI 0.94 to 0.97) between citrate and EDTA plasma upon correction for the dilution effect of the sodium citrate solution. Conclusions: These results indicate that the utilization of EDTA instead of citrate plasma is feasible and may provide similar diagnostic information. However, the observed variance could have an impact on clinical interpretation and risk assessment. Therefore, future studies are needed to confirm the results and, if necessary, determine cut-off values and clinical performance.